Facilitated transport of microplastics and nonylphenol in porous media with variations in physicochemical heterogeneity. (15th December 2022) - Xu, Lilin; Liang, Yan; Zhang, Rupin; Xu, Baile; Liao, Changjun; Xie, Tian; Wang, Dengjun
Abstract: Nonylphenol (Noph) has garnered worldwide concern as a typical endocrine disruptor due to its toxicity, estrogenic properties, and widespread contamination. To better elucidate the interaction of Noph with ubiquitously existing microplastics (MPs) and the potential interdependence of their transport behaviors, batch adsorption and column experiments were conducted, paired with mathematical modeling. Compared with sand, MPs and soil colloids show stronger adsorption affinity for Noph due to the formation of hydrogen bonding and the larger numbers of interaction sites that are available on solid surfaces. Limited amount of soil-colloid coating on sand grains significantly influenced transport behaviors and the sensitivity to solution chemistry. These coatings led to a monotonic increase in Noph retention and a nonmonotonic MPs retention in single systems because of the altered physicochemical properties. The mobility of both MPs and Noph was enhanced when they coexisted, resulting from their association, increased electrostatic repulsion, and competition on retention sites. Limited release of MPs and Noph (under reduced ionic strength (IS) and increased pH) indicated strong interactions in irreversible retention. The retention and release of Noph were independent of IS and solution pH. A one-site model with a blocking term and a two-site kinetic model well described the transport of MPs and Noph, respectively. Our findings highlight the essential roles of coexisting MPs and Noph on their transport behaviors, depending on their concentrations, IS, and physicochemical properties of the porous media. The new knowledge from this study refreshes our understanding of the co-transport of MPs and organic contaminants such as Noph in the subsurface. Graphical abstract: Image 1 Highlights: The coexistence of nonylphenol (Noph) and microplastic (MP) facilitates their transport. Soil colloids differentiate the trends of Noph/MP retention to ionic strength (IS). Physicochemical heterogeneity from soil colloids highly influences Noph/MP transport. MP transport is highly associated with Noph, IS, and collector surface roughness. ●Irreversibly retention occurred for Noph and the release is independent of IS/pH.